2020
DOI: 10.33411/ijist/2020020403
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Effluents and their Impacts on Human Health: Future of Industrial Boom

Abstract: Industries, being commercial productive units perform as manufacturing agents to produce large quantity of goods to cater the needs of increasing population. Manufacturing units use raw material and goods to deliver the final product. The findings of this research are consistent and reliable. The study area mainly consists of three types of industries including iron and steel, chemical and fertilizer and plastic industry. The hazardous waste generated by industries in Pakistan was computed as 1 lac tons per da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In contrast to the vast majority of strains of E. coli, this one produces toxins that can cause serious diseases and even death. Severe bloody diarrhea, non-bloody diarrhea, and stomach cramps are all common symptoms of infection [9]. Pakistan Council of Research in Water Resources (PCRWR) launched National Water Quality Monitoring Program (NWQMP) to monitor the water quality [10] [11], analyzed the water quality of different areas in Lahore and identified that the water was highly contaminated.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the vast majority of strains of E. coli, this one produces toxins that can cause serious diseases and even death. Severe bloody diarrhea, non-bloody diarrhea, and stomach cramps are all common symptoms of infection [9]. Pakistan Council of Research in Water Resources (PCRWR) launched National Water Quality Monitoring Program (NWQMP) to monitor the water quality [10] [11], analyzed the water quality of different areas in Lahore and identified that the water was highly contaminated.…”
Section: Introductionmentioning
confidence: 99%